Perancangan Sistem Informasi Parkir Di Universitas Dinamika Bangsa Berbasis Web - Anton Prayitno; Bima Syach Putra; Ikraam Arrela (LPPM Universitas Dinamika Bangsa, 2023)
Dinamika Bangsa University (UNAMA) is one of the tertiary institutions in Jambi City. The process of parking information at UNAMA is currently still being carried out manually. The absence of an information system certainly cannot compensate for the need for fast, precise and accurate presentation of information. In addition, manual data management is considered less effective for providing reports and information. Based on these problems, a website-based parking information system was designed to make it easier to manage parking information data such as controlling vehicles entering or leaving and making it easier for officers to know the number of vehicles being monitored computerized (online). In designing this system, object-oriented approaches are used such as use cases, activity diagrams and class diagrams. Data collection methods used are observation and interviews. The system development method used in this research is the waterfall method. With this parking system, it is hoped that it can help the campus performance in processing parking data and generating parking reports efficiently.